Effect of cured meat product ingredients on the Penicillium verrucosum growth and ochratoxin A production. (February 2019) - Andrade, María J.; Peromingo, Belén; Rodríguez, Mar; Rodríguez, Alicia
Abstract: Ochratoxigenic penicillia can grow on the cured meat products surface during their ripening. Ingredients added to cured meat products throughout their processing, and specifically of dry-fermented sausages, consist of a potential strategy to prevent or minimise the hazard associated with ochratoxin A (OTA) in these products. The aim of this work was to evaluate the effect of different concentrations of NaCl, KCl and sucrose in a conducive medium on the growth and OTA production by two Penicillium verrucosum strains. In general, there were no statistical differences between their growth rates. Although OTA production was not completely avoided in the presence of KCl and sucrose, it was reduced by comparison with NaCl. The concentration of the ingredients also affected the OTA production by P. verrucosum . These results would mean that the replacement of NaCl with KCl would imply the production of potentially safer cured meat products in terms of the OTA presence, which is of great importance for the current trends to reduce the NaCl levels in this kind of products. Furthermore, the addition of sucrose should be considered one of the approaches of the hurdle technology for minimising OTA accumulation in cured meat products. Highlights: The role of cured meat ingredients on mould growth and OTA production was evaluated. Two ochratoxigenic Penicillium verrucosum strains were investigated. Type and amount of cured meat ingredients influenced growth and OTA accumulation. Large differences between the tested two P. verrucosum strains were not found. Formulation changes might provide safer cured meats in terms of the OTA presence.